Why my disease is important: metrics of disease occurrence used in the introductory sections of papers in three leading general medical journals in 1993 and 2003 - Powles John W; Gouda Hebe N (BMC, 2011)
Abstract Background We assessed the metrics used in claims about disease importance made in the introductory sections of scientific papers published in 1993 and 2003. We were interested in the choice of metric in circumstances where establishing the relative social importance of a disease was, presumptively, a primary objective. Methods This study consisted of a textual examination of the introductory statements from papers retrieved from MEDLINE. Papers were published in the New England Journal of Medicine, The Lancet, and the Journal of the American Medical Association during the first halves of 1993 and 2003, and were selected on the basis of keywords found in a pilot study to be associated with claims about disease importance. Results We found 143 papers in 1993 and 264 papers in 2003 included claims about disease importance in their introductory sections, and characteristics of these claims were abstracted. Of the quotes identified in the papers and articles examined, most used counts, prevalence, or incidence measurements. Some also used risk estimates and economic quantities to convey the importance of the disease. There was no change in the types of metrics used between 1993 and 2003. Very few articles, even in 2003, used metrics that weighted disease onsets by the expected consequent loss of healthy time -- such as years of life lost, quality-adjusted life years, and/or disability-adjusted life years. Conclusions Claims about the relative importance of diseases continued to be overwhelmingly expressed in terms of counts (of deaths and disease onsets) and comparisons of counts, rates, and risks. Where the aim is to convey the burden that a given disease imposes on a society, "event-based" metrics might be less fit for the purpose than "time-based" metrics. More attention is needed to how the choice of metric should relate to the purpose at hand.